A unified model to optimize configuration of battery energy storage systems with multiple types of batteries. (1st June 2019) - Jiang, Yinghua; Kang, Lixia; Liu, Yongzhong
Abstract: Aiming to minimize the total cost of hybrid power system (HPS), a mathematical model for the configuration of battery energy storage system (BESS) with multiple types of batteries was proposed. The effects of battery types and capacity degradation characteristics on the optimal capacity configurations of the BESS and power scheduling schemes of the HPS were investigated. The effectiveness of the proposed model was verified and illustrated through a case study of a HPS with photovoltaic-wind-biomass-batteries. Results show that the optimal configuration of the BESS can be obtained by solving the proposed model, including the types and the capacities of batteries, and the power scheduling schemes of the batteries. For the integration of the HPS, the BESS with multiple types of batteries has certain economic advantages when compared with the BESS with a single type of batteries. In addition, the types and capacities of batteries in the BESS and the relative power scheduling schemes would change with the electricity curtailment rate of the renewable energy supply of HPS. The total cost of the HPS can be reduced at the expense of a certain amount of renewable energy supply. Highlights: A unified model is proposed for a BESS with multiple types of batteries. The optimal configuration and power scheduling scheme are determined simultaneously. The BESS with multiple types of battery is superior to the one with single battery type. The effects of variations in power supply on the optimal configuration are studied.